IMPLEMENTASI KEPEMIMPINAN PEMBELAJARAN OLEH KEPALA SEKOLAH UNTUK MEWUJUDKAN MUTU PENDIDIKAN DI SD NEGERI KEMUNING - Zahroh As Sakinah; Suherman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze and then describe how the implementation of instructional leadership by the principal in realizing the quality of education at SD Negeri Kemuning. In this research, the method used is qualitative with a case study approach. The data and information obtained in the study are the results of observation, interviews, and documentation activities. The findings of the study show that the instructional leadership by the principal in realizing the quality of education at SD Negeri Kemuning has been implemented effectively through optimal learning processes, supported by habituation activities, the P5 Silat Kaserangan program, and the mandatory extracurricular activity of Scouts, thus ensuring the quality of the school can be achieved.